1999
DOI: 10.3201/eid0501.990115
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Sin Nombre Virus in Western Colorado

Abstract: A mark-recapture longitudinal study of immunoglobulin G (IgG) antibody to Sin Nombre virus (SNV) in rodent populations in western Colorado (1994—results summarized to October 1997) indicates the presence of SNV or a closely related hantavirus at two sites. Most rodents (principally deer mice, Peromyscus maniculatus, and pinyon mice, P. truei) did not persist on the trapping webs much beyond 1 month after first capture. Some persisted more than 1 year, which suggests that even a few infected deer mice could ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
117
5
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 12 publications
11
117
5
3
Order By: Relevance
“…The presence of viral antigen in the kidneys was most common in deer mice that did not have antibodies to Sin Nombre virus, suggesting that virus shedding is greatest in the early stages of infection 32 . Also analogous to findings with the Old World hantaviruses, a higher sero-prevalence rate for Sin Nombre virus was observed in old deer mice than in young deer mice, with males infected more often than females [33][34][35] . Although these data are consistent with horizontal transmission by aggressive interactions and biting, they could also reflect the larger home range of adult males compared with adult females and the resulting increased risk of aerosol exposure 33 .…”
Section: Other Etiological Agentssupporting
confidence: 78%
“…The presence of viral antigen in the kidneys was most common in deer mice that did not have antibodies to Sin Nombre virus, suggesting that virus shedding is greatest in the early stages of infection 32 . Also analogous to findings with the Old World hantaviruses, a higher sero-prevalence rate for Sin Nombre virus was observed in old deer mice than in young deer mice, with males infected more often than females [33][34][35] . Although these data are consistent with horizontal transmission by aggressive interactions and biting, they could also reflect the larger home range of adult males compared with adult females and the resulting increased risk of aerosol exposure 33 .…”
Section: Other Etiological Agentssupporting
confidence: 78%
“…Numerous studies have demonstrated an age-related prevalence of antibody, often favoring males (Glass et al, 1988;Childs et al, 1994;Mills et al, 1997;Calisher et al, 1999), indicating that virus is maintained in reservoir populations via horizontal transmission, perhaps most frequently through aggressive encounters among adult males. Populations consisting of older individuals may have much higher prevalences of infection than populations comprising mostly young mice.…”
Section: Introductionmentioning
confidence: 99%
“…Populations consisting of older individuals may have much higher prevalences of infection than populations comprising mostly young mice. It has been hypothesized that transseasonal maintenance of hantaviruses in reservoir populations in temperate environments occurs via longlived resident animals, which maintain infection from the previous season and reintroduce virus to susceptible animals each spring (Abbott, et al, 1999;Calisher et al, 1999;Mills et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…After the discovery of this disease in the southwestern United States 1,2 in 1993, several long-term studies of reservoir populations were initiated-in part, to develop measures to control and prevent human infection. 3 Four studies were conducted in the Southwestern United States [4][5][6][7] and one in Montana. 8 An important potential tool for preventing HPS is the use of models based on environmental and ecological conditions that predict risk of HPS.…”
Section: Introductionmentioning
confidence: 99%